Competitive Potential of Sal (Shorea robusta) Seedlings - Srivastava, P. B. L. (Indian Forester, 1972)
The present investigation describes the competing effect of some common associates on the growth and nutrient uptake of sal seedlings when applied wilh nitrogen, pbosphorus and potassium fertilizers. The studies indicate that different competing species Influence growth and nutrient uptake in different manner. Moghania chappar and Murraya koenigil are not harmful as competitors in addition to being good regeneration indicators. Mallotus philippensis is not a specific site indicator due to its wide ecological amplitude but a good associate of sal. Clerodendrum viscosum and Syzygium cumini are good site indicators but are bad associate of sal as their presence resulted in suppression of growth and nutrient uptake of the latter. It Is essential to remove these species from good sites once their indicator value has been made use of. Further, in this type of soil application of nitrogenous fertilizers or a silvlcultural technique which increases its availability may prove beneficial to sal seedlings. On the contrary, application of phosphorus and potassium fertilizers did not prove beneficial to the growth of sal seedlings.